Sine Exponential Formulation/Real Domain

From ProofWiki
Jump to navigation Jump to search

Theorem

For any real number $x \in \R$:

$\sin x = \dfrac {e^{i x} - e^{-i x} } {2 i}$

where:

$e^{i x}$ denotes the exponential function
$\sin x$ denotes the real sine function
$i$ denotes the inaginary unit.


Proof 1

Recall the definition of the sine function:

\(\displaystyle \sin x\) \(=\) \(\displaystyle \sum_{n \mathop = 0}^\infty \paren {-1}^n \frac {x^{2 n + 1} } {\paren {2 n + 1}!}\)
\(\displaystyle \) \(=\) \(\displaystyle x - \frac {x^3} {3!} + \frac {x^5} {5!} - \frac {x^7} {7!} + \cdots + \paren {-1}^n \frac {x^{2 n + 1} } {\paren {2 n + 1}!} + \cdots\)


Recall the definition of the exponential as a power series:

\(\displaystyle \exp x\) \(=\) \(\displaystyle \sum_{n \mathop = 0}^\infty \frac {x^n} {n!}\)
\(\displaystyle \) \(=\) \(\displaystyle 1 + \frac x {1!} + \frac {x^2} {2!} + \frac {x^3} {3!} + \cdots + \frac {x^n} {n!} + \cdots\)


Then, starting from the right hand side:

\(\displaystyle \frac {e^{i x} - e^{-i x} } {2 i}\) \(=\) \(\displaystyle \frac 1 {2 i} \paren {\sum_{n \mathop = 0}^\infty \frac {\paren {i x}^n} {n!} - \sum_{n \mathop = 0}^\infty \frac {\paren {-i x}^n} {n!} }\)
\(\displaystyle \) \(=\) \(\displaystyle \frac 1 {2 i} \sum_{n \mathop = 0}^\infty \paren {\frac {\paren {i x}^n - \paren {-i x}^n} {n!} }\)
\(\displaystyle \) \(=\) \(\displaystyle \frac 1 {2 i} \sum_{n \mathop = 0}^\infty \paren {\frac {\paren {i x}^{2 n} - \paren {-i x}^{2 n} } {\paren {2 n}!} + \frac {\paren {i x}^{2 n + 1} - \paren {-i x}^{2 n + 1} } {\paren {2 n + 1}!} }\) split into even and odd $n$
\(\displaystyle \) \(=\) \(\displaystyle \frac 1 {2 i} \sum_{n \mathop = 0}^\infty \frac {\paren {i x}^{2 n + 1} - \paren {-i x}^{2 n + 1} } {\paren {2 n + 1}!}\) as $\paren {-i x}^{2 n} = \paren {i x}^{2 n}$
\(\displaystyle \) \(=\) \(\displaystyle \frac 1 {2 i} \sum_{n \mathop = 0}^\infty \frac {2 \paren {i x}^{2 n + 1} } {\paren {2 n + 1}!}\) as $\paren {-1}^{2 n + 1} = -1$
\(\displaystyle \) \(=\) \(\displaystyle \frac 1 i \sum_{n \mathop = 0}^\infty \frac {\paren {i x}^{2 n + 1} } {\paren {2 n + 1}!}\) cancel $2$
\(\displaystyle \) \(=\) \(\displaystyle \frac 1 i \sum_{n \mathop = 0}^\infty \frac {i \paren {-1}^n x^{2 n + 1} } {\paren {2 n + 1}!}\) as $i^{2 n + 1} = i \paren {-1})^n $
\(\displaystyle \) \(=\) \(\displaystyle \sum_{n \mathop = 0}^\infty \paren {-1}^n \frac {x^{2 n + 1} } {\paren {2 n + 1!} }\) cancel $i$
\(\displaystyle \) \(=\) \(\displaystyle \sin x\)

$\blacksquare$


Proof 2

Recall Euler's Formula:

$e^{i x} = \cos x + i \sin x $


Then, starting from the right hand side:

\(\displaystyle \frac {e^{i x} - e^{-i x} }{2 i}\) \(=\) \(\displaystyle \frac {\paren {\cos x + i \sin x} - \paren {\cos \paren {-x} + i \sin \paren {-x} } } {2 i}\)
\(\displaystyle \) \(=\) \(\displaystyle \frac {\paren {\cos x + i \sin x - \cos x - i \sin \paren {-x} } } {2 i}\) Cosine Function is Even
\(\displaystyle \) \(=\) \(\displaystyle \frac {i \sin x - i \sin \paren {-x} } {2 i}\)
\(\displaystyle \) \(=\) \(\displaystyle \frac {i \sin x - i \paren {-\sin \paren {-x} } } {2 i}\) Sine Function is Odd
\(\displaystyle \) \(=\) \(\displaystyle \frac {2 i \sin x} {2 i}\)
\(\displaystyle \) \(=\) \(\displaystyle \sin x\)

$\blacksquare$


Proof 3

\(\text {(1)}: \quad\) \(\displaystyle e^{i x}\) \(=\) \(\displaystyle \cos x + i \sin x\) Euler's Formula
\(\text {(2)}: \quad\) \(\displaystyle e^{-i x}\) \(=\) \(\displaystyle \cos x - i \sin x\) Euler's Formula: Corollary
\(\displaystyle \leadsto \ \ \) \(\displaystyle e^{i x} - e^{-i x}\) \(=\) \(\displaystyle \paren {\cos x + i \sin x} - \paren {\cos x - i \sin x}\) $(1) - (2)$
\(\displaystyle \) \(=\) \(\displaystyle 2 i \sin x\) simplifying
\(\displaystyle \leadsto \ \ \) \(\displaystyle \frac {e^{i x} - e^{-i x} } {2 i}\) \(=\) \(\displaystyle \sin x\)

$\blacksquare$


Also presented as

This result can also be presented as:

$\sin x = \dfrac 1 2 i \paren {e^{-i x} - e^{i x} }$


Also see


Sources